The Impact of the Eight-Week High-Intensity Interval Training Implemented by the National Track and Field Team on Some Motor Skills by Gender - Serdar Adigüzel; Baykal Karataş; Burak Yücel (Journal of Educational Issues, 2024)
Purpose: This study aims to study the impact of the eight-week high-intensity interval training implemented by the national track and field team on some motor skills by gender. Technique and method: The study involves 17 male and 16 female athletes ages 18 to 26 who currently pursue an active sports life in the Turkish national crosscountry teams. The anaerobic strength, agility, vertical and horizontal jump values, and sprint skills of the athletes in the study were measured. Findings: Through statistical assessment, it was found that while there was a significant increase in the Wingate test, it was not significant in terms of gender. It was also found that while significant decreases took place in the right-foot jump, left-foot jump, right-foot vertical jump, left-foot vertical jump, double-foot vertical jump, Illinois agility test, and sprint test values, there were no significant differences based on gender. Conclusion: The study suggests that an eight-week high-intensity interval training boosts the anaerobic capacities of young female and male national cross country athletes and improve performance parameters such as jump and vertical jump performance, agility, and sprint.